2003
DOI: 10.1038/sj.cgt.7700648
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 gene therapy combined with hyperthermia using magnetic nanoparticles

Abstract: Heat shock proteins (HSPs) are recognized as significant participants in immune reactions. We previously reported that expression of HSP70 in response to hyperthermia, produced using our original magnetite cationic liposomes (MCLs), induces antitumor immunity. In the present study, we examine whether the antitumor immunity induced by hyperthermia is enhanced by hsp70 gene transfer. A human hsp70 gene mediated by cationic liposomes was injected into a B16 melanoma nodule in C57BL/6 mice in situ. At 24 hours aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 41 publications
1
42
0
1
Order By: Relevance
“…However, traditional heating temperature had achieved non-ideal therapeutic effect; in fact, some researchers had reported that traditional methods promoted the growth of tumor cells (25)(26)(27)(28). Nevertheless, in the present study, we have found a novel and potentially useful technique in applying magnetic fluid hyperthermia (MFH) on mouse pancreatic cancer models using a unique mouse pancreatic cancer cell line (MPC-83), established by us in 1983.…”
Section: Introductionmentioning
confidence: 83%
“…However, traditional heating temperature had achieved non-ideal therapeutic effect; in fact, some researchers had reported that traditional methods promoted the growth of tumor cells (25)(26)(27)(28). Nevertheless, in the present study, we have found a novel and potentially useful technique in applying magnetic fluid hyperthermia (MFH) on mouse pancreatic cancer models using a unique mouse pancreatic cancer cell line (MPC-83), established by us in 1983.…”
Section: Introductionmentioning
confidence: 83%
“…An acute excess achieved by repeated Hsp70 gene transfer alone or in combination with hyperthermia proved to kill large established melanoma or to arrest tumor growth in mice, respectively [44,58]. Alternatively, an acute excess of Hsp70 induced by different therapies of human melanomas [1,43] may be utilized to stimulate the immune system against resistant tumor populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since HSPs function as natural and powerful immunostimulants, recombinant HSP70 therapy 64) or HSP70 gene therapy 65) could be a possible approach. For recombinant HSP70 therapy, MCLs and recombinant mouse HSP70 were injected into melanoma nodules in C57BL/6 mice, which were subjected to hyperthermia at 43°C for 30 min.…”
Section: Development Of Novel Cancer Immunotherapy Based On Heat-indumentioning
confidence: 99%